To study the turnover problem in Smart Glove Corporation Sdn Bhd / Siti Salwa Jumari - Jumari, Siti Salwa (2008)
The case study in this topic is about the turnover problem in Smart Glove Corporation Sdn Bhd. The turnover problem, will give the bad image to the company. Besides that it will increase the cost of to hiring new workers. Many factors can caused to turnover which are the job dissatisfaction, environment working condition, merging company, lack of compensation benefit, lack of facilities and many more. The findings showed the comparison from what that has been presented in the literature review with the current practice or existing scenario in the area of study. The similarities between the issues that exist in the company relating to the turnover and any contradicting facts will be highlighted. The findings that can be finding are from the recruitment process, compensation benefit and the job satisfaction.